Colon liver metastasis complicated with tumor thrombus in the bile duct: A case report. (2018) - Watanabe, Yoshifumi; Tamagawa, Hiroshi; Mizushima, Tsunekazu; Taniguchi, Eiji; Kikkawa, Hiroyuki; Sasaki, Masaru; Nakaba, Hiroyuki
Highlights: Colorectal liver metastasis with bile duct tumor thrombus is rare in clinical. Hepatectomy is a common therapeutic procedure for colorectal liver metastasis. Colorectal liver metastasis with bile duct tumor thrombus might be a bad prognosis. Abstract: Introduction: Hepatectomy including conversion therapy is recommended for colorectal liver metastasis (CRLM). CRLM complicated with bile duct tumor thrombus (BDTT) is rare, even though there are more opportunities to perform hepatectomy for CRLM in recent years. Presentation of case: A 76-year-old Japanese man with a history of right hemicolectomy for ascending colon carcinoma presented with a portal hepatic tumor and the dilatation of the right bile duct found by computed tomography (CT) eighteen months after the colectomy. Magnetic resonance imaging confirmed a tumor in liver segment VIII, and magnetic resonance cholangiopancreatography and endoscopic retrograde cholangiopancreatography showed a mass in the hilar bile duct. Bile cytology did not prove carcinoma. The patient underwent right and caudate lobectomy with extrahepatic biliary tract resection plus hepaticojejunostomy. Histopathological examination revealed that both the tumor in liver segment VIII and the BDTT comprised moderately differentiated tubular adenocarcinoma, originating from the previous colon carcinoma. Six months after hepatectomy, CT revealed tumor recurrence in the residual intrahepatic bile duct. Radiation therapy was administered for the recurrent lesion, which reduced the tumor size temporarily. Despite the multimodal therapy, the disease progressed and the patient died one year after the hepatectomy. Discussion: Some studies reported no correlation between CRLM bile duct invasion and clinical outcomes, but there is no available evidence focused on BDTT which is of an advanced stage in the bile duct invasion. Conclusion: Hepatectomy is a common therapeutic procedure for CRLM, but CRLM with BDTT might be associated with a bad prognosis.